FORMULATION AND EVALUATION OF A TASTE-MASKED METRONIDAZOLE ORAL SUSPENSION USING OKRA GUM AND ION EXCHANGE RESINS - Ayush Mazumder,; Jasmine Bhuyan,; Lauv Arnav,; Dhruv Singh,; Dr.H.Gayathri, (The Bioscan, 2026)
Metronidazole (MNZ) is a widely used antibiotic effective against anaerobic bacteria and protozoa. However, its bitter taste poses challenges for patient compliance, especially among pediatric populations.